2019
DOI: 10.1186/s13578-019-0325-8
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer cells secrete exosomes to promote self-proliferation by shortening mitosis duration and activation of STAT3 in a hypoxic environment

Abstract: Colon-cancer-cell-derived exosomes (CDEs) are emerging mediators of tumorigenesis and serve as messengers of intercellular communication; however, whether the CDEs affect the proliferation of colon cancer cells themselves remains unknown. In the current study, the CDEs isolated from human colon cancer cell line SW480 and HCT116 showed a size range of 60–150 nm, typical bilayer-encapsulated vesicles, and expressed the exosomal markers CD81 and CD63. Incubation of SW480 cells with CDEs labelled with PKH67 fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…The highly malignant behaviour of colon cancer cells is closely associated with the activity of JAK/STAT pathway. 35 Our data indicated that OCA treatment repressed the activation of JAK2/STAT3 pathway in colon cancer cells, which was further confirmed by IF staining, showing increased levels of STAT3 protein located in the cell cytoplasm. In addition, restoration of JAK2/STAT3 signalling by colivelin and IL-6 abolished OCA-mediated proliferation and invasion inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…The highly malignant behaviour of colon cancer cells is closely associated with the activity of JAK/STAT pathway. 35 Our data indicated that OCA treatment repressed the activation of JAK2/STAT3 pathway in colon cancer cells, which was further confirmed by IF staining, showing increased levels of STAT3 protein located in the cell cytoplasm. In addition, restoration of JAK2/STAT3 signalling by colivelin and IL-6 abolished OCA-mediated proliferation and invasion inhibition.…”
Section: Discussionsupporting
confidence: 78%
“…These EVs are taken up by the same cells (i.e., in autocrine feedback loop), and are able to affect their growth and survival in a time- and concentration-dependent manner [ 114 ]. In addition, Ren et al 2019 found that EVs derived from colon cancer cells accelerated cell division, which in turn contributed to disease progression [ 124 ]. Another study examining gastric cancer EVs also found increased cell proliferation in a time and concentration manner through activation of Akt and ERK, and PI3k pathways [ 125 ].…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Moreover, Ren et al [ 31 ] have reported that self-growth or proliferation through exosome secretion, especially under hypoxic conditions, by reduction of the mitosis and activation duration can be promoted by CRC cells. In a recent study, the CRC cell-derived exosomes are separated from human colon cancer cell line SW480 and HCT116.…”
Section: Leading Roles Of Exosomes In Crcmentioning
confidence: 99%